Pendampingan Kader Posyandu Pada Program Pemberian Makanan Tambahan (PMT) Lokal di Puskesmas Mata Kota Kendari - Rosnah, Rosnah; Yunanci V. Gobel, Sri; Ahmad; Sake, Risma; Irma, Rita; Fathurrahman, Teguh; Hasan; Syahrianti (Poltekkes Kemenkes Kendari, 2025)
Stunting is a chronic nutritional problem that remains a challenge in Kendari City. One prevention strategy is through a local food-based Supplementary Feeding (PMT) program supported by Posyandu (Integrated Service Post) cadres. This community service program aims to improve the cadres' capacity in processing, serving, providing nutrition education, and assisting families of toddlers. Implementation methods included training, hands-on practice, and on-the-job mentoring for 30 Posyandu cadres in the Mata Community Health Center (Puskesmas Mata) work area. Evaluation was conducted through pre- and post-tests, as well as skills observations. Pre-and post-test data were analyzed quantitatively to illustrate improvements in participants' knowledge scores, while observation and interview results were analyzed qualitatively to determine changes in cadres' behavior and practical skills. Data are presented in tables and narratives explaining the achievements in improving the Posyandu cadres' capacity. Results show an increase in the average cadre's knowledge from 62.4 to 88.6, as well as significant improvements in skills in local food processing and nutrition education. This activity effectively strengthens the role of Posyandu cadres in implementing local PMT, in accordance with the 2023 Ministry of Health Technical Guidelines, to accelerate stunting reduction.